The Renovationist Schism in the Don Region and the Activities of «Archbishop» Melchizedek (Nikolayev) - Shadrina Alla (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
The article deals with the history of the renovationist schism in the Diocese of Don and Novocherkassk and with the role played in that process by “Archbishop” Melchizedek (also known as Nikolayev, Nikolev, or Nikolin). Based on a wide range of archive sources and materials of the 1920s periodicals, the author shows that the renovationist schism in the Don area was initiated by “Archbishop” Melchizedek supported by the State Political Directorate of Don Oblast. On 18 June 1922, supported by that governmental body, there was established an eparchial renovationist committee in Novocherkassk, which was the reason why Archbishop Mitrofan (Simashkevich) refused to be the head of the Diocese any longer. The renovationism localized in Novocherkassk started to spread all over the Diocese only after the arrest of the opposition Novocerkassk clergy. The parish priests who obeyed submissively to the authority of “Archbishop” Melchizedek were misinformed and so believed that he was the legitimate successor of Metropolitan Mitrofan who had “retired”. Regardless of the fast dissemination of renovationism, there were no radical reforms in the Don area as both the priests and the church people of the Diocese of Don and Novocherkassk were quite conservative. After Patriarch Tikhon had been released from prison on 26 June 1923, there started spontaneous anti-renovationist movement, both among the priests and the active laity who were not numerous though. The decisive organizational stage for the movement was the episcopal cheirotonia of Archpriest Zacharia Lobov. The coming of an active bishop to the church helm became the reason both for Metropolitan Mitrofan’s return to the church administration and eparchial parishes. And the big number of the Don parishes leaving the renovationist church administration were the reason for the arrests of Bishop Zacharia and his most active followers.